Correction: G3BP1, G3BP2 and CAPRIN1 Are Required for Translation of Interferon Stimulated mRNAs and Are Targeted by a Dengue Virus Non-coding RNA. - Katell Bidet; Dhivya Dadlani; Mariano A Garcia-Blanco (PLoS Pathogens, 2017)
[This corrects the article DOI: 10.1371/journal.ppat.1004242.].